Projeto, Construção e Validação de um Sistema de Compressão Uniaxial para Estimativa da Compactação do Solo - Weiss, Almiro (2005)
The compaction of the agricultural soils has worldwide importance because of the increasing of the farm with machinery resulting in the increasing of heavy machines for cultivation system, mainly, in the developed countries. The term, soils compaction refers to the compression carried out on the non-saturated soil, during which an increase of bulk density exists, producing the reduction of its volume of pores like a consequence. The excessive compaction has damaging consequences for the agriculture and environmental. For this reason, the state of soils compacting has received enough attention from researchers and agricultural farmers. The uniaxial compression has been used for predicting the agricultural soils compaction with so much efficiency. In accordance to the previous exposure, in this paper aimed the to develop an apparatus of uniaxial compression of the soil for testing in laboratory and evaluating its performance. The apparatus is composed by a pneumatic press, where the sample of soil is packaged in a metallic volumetric ring (made in steel carbon - ABNT 1020), with thickness of wall of 0,2 cm, internal diameter of 7,0 cm and two options of height of 2,4 cm and 4,8 cm. Cyclical loads of compression were applied to the sample in order to verify the variation of the soil deformation. A lineal transducer detects the samples behavior during the compression and uncompression (relaxation) uniaxial indicating in the digital counter s display the variations of measure of the sample deformation. Successive loads of 150, 200, 300, 400, 500, 600, 700 and 800 kPa were applied in periods of 60 s for compression and 120 s for uncompression of the sample. The results allowed conclude that the system presents answers with good precision and greater versatility with the variation of de samples size for compression.